Desenvolvimento de um sistema digital na perspectiva do Desenho Universal para a Aprendizagem (DUA): formação de professores para elaboração de planos de aula - Mendoza, Babette de Almeida Prado (Universidade Federal de São Carlos, 2022)
This research aimed to plan, develop and evaluate a prototype of a digital system designed to guide, in a self-directed way, the elaboration of a lesson plan that applies the principles of Universal Design for Learning from the perspective of Inclusive Education. The Inclusive Education perspective seeks to make effective the full inclusion of all students in regular classes since Early Childhood Education. Therefore, the regular education teacher at different levels must seek to respond adequately to the specific demands of students with disabilities, global developmental disorders, and high abilities/giftedness, and these must also be aligned with the demands of other students who have specific characteristics. and different learning styles, skills, repertoires and levels of difficulty. The research problem of the present study derives from this context, as it starts from the observation that there is a repressed demand for continuing teacher education programs that deal with this reality experienced by regular education teachers. Unlike Brazil, solutions based on general strategies as proposed by the Universal Design for Learning, and not only on individualized adaptations, have been applied as effective pedagogical practices for more than two decades in other countries. For the theoretical basis on Universal Design for Learning, publications from the Center for Applied Special Technology (CAST) were used, which is the main leader in research and training, responsible for conceptually outlining, researching and training teachers and managers in Universal Design for Learning (UDL). This is a research of mixed nature, qualitative and quantitative, exploratory and descriptive. The study consists of the following stages: the first stage was composed of the planning, development and evaluation of a virtual continuing education program for 32 teachers of regular classes of elementary school - cycle I - and for AEE teachers, in order to guide them and motivate them to collaboratively develop lesson plans with Universal Design for Learning; the second stage consisted in the development of a prototype of a medium fidelity digital system that allows the teacher to be able to individually or collaboratively, in a self-directed way, develop a lesson plan with DUA, this development adopted the User-Centered Design methodology; and the third stage was the evaluation of the prototype by two groups of judges (with technical profile and end-user profile). Adding the scores of very satisfactory and satisfactory to the question about the study dynamics and training activities (7% and 65% respectively), we obtained 95% approval and part of this course study material was adjusted to be available on the prototype. The evaluation of the interface and functionality of the prototype were positive, and it was also considered that the guidelines provided met the proposed objective. Based on Heuristic Analysis and Usability Testing, the two groups of judges evaluated that the prototype responds to Niensen's 10 heuristics and that the observations raised by the evaluators refer to elements of low severity, which do not interfere with navigation and execution and that do not need immediate correction. The research suggested that the digital prototype would be viable as a resource to support initial and continuing teacher training programs on Universal Design for Learning from the perspective of Inclusive Education.
Development of a digital system from the Universal Design for Learning (UDL) perspective: training teachers to develop class plans
Keywords: Educação especial; Inclusão escolar; Desenho universal para a aprendizagem; Formação de professores; Planos de aula; Sistema digital; Special education; School inclusion; Universal design for learning; Continuing teacher training; Lesson plans; Digital prototype; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL